Innovative application of an implantable venous access system in the portal vein: technique, results and complications in three dogs - Kiona S. de Nies; Hedwig S. Kruitwagen; Giora van Straten; Leonie W. L. van Bruggen; Joris H. Robben; Baukje A. Schotanus; Ies Akkerdaas; Anne Kummeling (BMC Veterinary Research, 2019)
Abstract Background Vascular access port (VAP) systems are widely used in human medicine to provide long-term venous access. However, in veterinary medicine the use of VAP systems is not common practice and publications on their potential applications have been limited. A VAP system was used as part of an experimental study on liver regeneration and implanted in the canine portal vein to create direct access to the portal venous circulation of the liver. The aim of the present study is to describe the surgical technique, its use, and the complications of a VAP system in three research dogs. Results The VAP system was successfully used for the intraoperative measurement of portal blood pressure, the administration of cell suspensions, and the collection of portal venous blood samples. Long-term complications consisted of dislocation of the VAP system in one dog (2 months after implantation) and thrombus formation at the catheter tip in two dogs (3 months after implantation). Both complications prevented further use of the VAP but had no adverse clinical implications. Conclusions This pilot study suggests that the VAP system is an effective and safe technique to obtain long term access to the portal venous system in dogs. However, complications with port detachment and thrombosis may limit long term use of VAPs in the portal system of dogs.